Innovation in the anthropological perspective insights and consequences for the theory, practice, and design of innovating - Gluesing, Julia C.; Miller, Christine; Wild, Helga (Routledge, 2025)
Innovation is a constant in human life and organization, arising from within a context-based culture of social structures and beliefs. This book re-examines the processes, practices, and mechanisms of innovation from an anthropological perspective, offering a theory of innovation as a dynamic multidimensional system
Keywords: Ethnologie; Erfindung; Innovation; Angewandte Anthropologie